Chinese market entry possibility by the means of joint ventures. - Peter, Gysler Andreas. (2009)
Worldwide foreign direct investment(FDI) has grown at an average of 15.7% between 1970 and 2005 and still today is an important driver for the globalisation process (UNCTAD, 2006). It is the large firms, however,that have been its main drivers (Buckley, 1997; Eden & Levitas, 1997; Fujita, 1995). Small and medium enterprises (SMEs) do face high barriers when considering engaging in FDI activities and are more likely to fail in comparision to a large multinational enterprises (MNEs) (Acs & Mock, 1997; Eden & Levitas, 1997). These barriers stem from the fact that SMEs oftentimes dispose of only limited resources, in particular limited financial, information and managerial resources and hence have a different attitude towards risk (Kirby & Kaiser, 2003). Such resource limitations, however, can be overcome by the means of forming a Joint Venture (JV).